Upcycling of brewer’s yeast - Application as material for encapsulating unstable liquid ingredients in the food industry - Eigenfeld, Marco; Kerpes, Roland; Bez, Jürgen; Becker, Thomas (BrewingScience, 2020)
Encapsulation refers to the process of equipping an active compound with a relevant wall material in order to protect it. Owing to the flexible protein structure combined with rigid polysaccharide content, yeast cell walls are considered ideal for encapsulation. Additionally, the low price and availability are further advantages that render yeast cells a suitable material for encapsulation. However, since yeast cells used in the brewing process retain a bitter taste from the adsorption of iso-α-acids, it is essential to upcycle spent brewer’s yeast prior to its possible application as an encapsulation material. The upcycling process presented here was carried out in three main stages: (i) debittering, (ii) fragmentation of spent brewer’s yeast and (iii) encapsulation by using yeast cell wall fragments. A maximum removal of bitterness of 78.08 % was identified at 6 ?C, pH 9 and after 30 min of debittering. The average residual bitterness was 0.51 ± 0.12 mg Iso- α/L∙g wet weight. Three subsequent sessions of high-pressure homogenization at 800 bar were appropriate to achieve maximum cell disruption of more than 90 % and a D0 (50) value of 0.0875 μm. A high encapsulation efficiency, determined in encapsulation trials with seed oil, indicated that yeast cell walls are suitable as material for encapsulating fatty acids and can replace or even exceed the gum arabic reference system. Encapsulation of more than 90 % of the initial amount of oil were possible. The results obtained from the experiment suggest that the employment of high-pressure homogenisation at optimal temperature and pressure achieved maximum encapsulation efficiency and that yeast cell wall fragments can be considered as an appropriate substitute for gum arabic.